Comparison of the Progression of Localized Retinal Nerve Fiber Layer Defects in Red-free Fundus Photograph, En Face Structural Image, and OCT Angiography Image - Ji, Min Jung; Park, Ji-Hye; Yoo, Chungkwon; Kim, Yong Yeon (Journal of glaucoma, 2020)
This study demonstrated the high topographic correlation between the red-free fundus photographs and en face structural images in eyes with glaucomatous progression. The purpose of this study was to compare the progression of localized retinal nerve fiber layer (RNFL) defects in red-free fundus photographs, en face structural images, and optical coherence tomography angiography (OCTA) images. We performed a retrospective, comparative study on 45 glaucomatous eyes showing RNFL defect widening in red-free photography. The localized RNFL defect in the red-free photographs was termed as red-free defect. The wedge-shaped hyporeflective area radiating from the optic nerve head in the optical coherence tomography (OCT) en face structural images and OCTA images was defined as en face defect and OCTA defect, respectively. The baseline and follow-up angular parameters of each red-free defect were compared with those of en face defect and OCTA defect. When the baseline angular parameters were compared, there were no significant differences between red-free defect and en face defect, and between red-free defect and OCTA defect (all, P>0.017). In addition, the follow-up angular parameters showed no difference between red-free defect and en face defect. However, the OCTA defect showed significantly greater values compared with red-free defect and en face defect with respect to the distal angular location and angular width at follow-up visit (36.78±15.10 vs. 34.10±15.09 vs. 33.40±15.05 degrees, both, P<0.001). Localized RNFL defects detected in red-free photographs showed high topographic correlation with defects detected in OCT en face structural images, and this correlation was also noted in eyes with progressive glaucoma. The OCT en face structural images may be an alternative to red-free photography for identifying progressive RNFL defects in eyes with glaucoma.